Education Profile of Children in Families Post-Eruption of Sinabung in the Karo Regency, Indonesia - Elfina, Susy; Dung, Anh; Dao, Bitch Cay (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The eruption of Mount Sinabung causes damage and loss, especially in education. Education was blocked that caused by the factors of parents and children themselves who are responsible for the development and education of children as a matter of education in the family and also the problem of the continuity of the child's learning. This research was descriptive research that uses the method of field observation, interview, and documentation. The main instrument that uses in the field of collecting the data was a questionnaire. The subject of this research were students and parents at SMA N 1 Simpang Empat. From the research, the presence of children in the family educational issues such as sources of funds (for the continuity of children's learning), and Problems Psychologist Parents (Post-eruption of Mount Sinabung) and also there is that there were some problem that Against Child Survival Learning These include: limited transportation, finance, atmosphere learning and time. As for overcoming this issue either from the government itself as scholarships for school children, as well as from the non-governmental donations from individual or group of people.